The analysis of ‘ make or buy’ decisions and the related business policies in the communications industry both in Turkey and around the world - Heper, Burcu (My University, 2000)
unknown
Keywords: İLETİŞİM; İletişim (Telekomünikasyon); TELEKOMÜNİKASYON